Library data visualisation transformations: global patterns for research evaluation metrics in China - Wu, Cocoa; Kennedy, Aaron; Qiu, Lulu; Smyth, Neil (2019)
The new information environment in higher education libraries is shaped by an ever changing scholarly communication infrastructure and evolving cycles of research production, communication and evaluation. New services have emerged for research data analytics, based around strategic research intelligence. This paper focuses on library data visualisation transformations for research evaluation metrics in physical library spaces using physical hardware technologies and software, notably, in this study, CiteSpace and Google Fusion Table. This paper focuses on research evaluation metrics and the evolution of a data analytics service in China. Data-driven research intelligence is an emerging need for universities, including reporting to funding organisations. Deeper understandings of collaborative authorship and citation clusters can provide a comparative edge for strategy development. Leading universities need research data to analyse the performance at multiple levels. This paper focuses on data visualisation in the physical library using wall and table technologies. It showcases how library atrium spaces are transformed through the data visualisation of bibliometric data, where the data can be presented in ways that are beautiful, boring and functional. The paper will demonstrate how library spaces create opportunities for interaction, where researchers can experience data or interact and manipulate data to create new meaning, narratives and stories. The paper presentation will include video examples of data visualisation and the visualisation of data in physical library spaces, projecting a future for data visualisation in new library buildings on university campuses.